If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9m + -14 = -17 + 8m Reorder the terms: -14 + 9m = -17 + 8m Solving -14 + 9m = -17 + 8m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-8m' to each side of the equation. -14 + 9m + -8m = -17 + 8m + -8m Combine like terms: 9m + -8m = 1m -14 + 1m = -17 + 8m + -8m Combine like terms: 8m + -8m = 0 -14 + 1m = -17 + 0 -14 + 1m = -17 Add '14' to each side of the equation. -14 + 14 + 1m = -17 + 14 Combine like terms: -14 + 14 = 0 0 + 1m = -17 + 14 1m = -17 + 14 Combine like terms: -17 + 14 = -3 1m = -3 Divide each side by '1'. m = -3 Simplifying m = -3
| 1.17y=5.85 | | 2m(3m+13)= | | (2+10)xc-6= | | -28.99+x=-55.03 | | -4y=1x+48 | | P=48-Q | | 26.4+q=61.7 | | (3-v)(3v+1)=0 | | X-13.14=69.17 | | k-7+2k+19=2k+4+2k | | e(-6*w)=95 | | e^2=95 | | 3+7k=5k-7 | | 4x+12y=62 | | -97=5(1-7a)+3 | | 4x-8=4x+3 | | X+.05X=119.95 | | -7x-7x=56 | | -14+3n=4(n-3) | | 2x-18=6(7-3x) | | 7+22x+3x^2=0 | | 12z-4=11z+4 | | -7x+7x=56 | | 8(1-3n)=-112 | | 9r(r+5)= | | 25q-(25q+40000)=0 | | 63x^4+126x^3+35x^2=0 | | 4+3n=20+7n | | =-0.3x^2+3x+4 | | 8x-(6-2x)=2x-6 | | G(x)=-0.3x^2+3x+4 | | m^2+4.5m-2.5=0 |